Vluchtschansen in Midden-Limburg. Boerenschansen uit de 16de en 17de eeuw als schuilplaatsen voor de plattelandsbevolking (Bulletin KNOB, 2020)
In the southern provinces of the Netherlands and the neighbouring parts of Belgium traces have been discovered of an interesting group of 'farmers' entrenchments', small fortifications from the Early Modern Period. Between the sixteenth and eighteenth century, a period of frequent warfare. many villages and hamlets built simple fortifications as refuges for the population and their cattle. Some of these refuges were located close to the villages, other examples were  built in less accessible terrains such as stream valleys.In this article, an inventory of these small fortifications for one of the core regions, the central part of the Dutch province of Limburg, is presented. Two examples are studied in some more detail: the refuges of Boshoven and Laar (municipality of Weert). At Boshoven, part of the archive still exists. This object is remarkable, as the oldest cadastral map (c.1830) still shows how every inhabitant of the village owned a tiny plot within the refuge. At Laar, a small archaeological survey was executed. following a request from the village for input for a planned restoration project.